Вплив насичуваності споживачів на умови досягнення рівноваги в економічній системі - Makhort, А. F. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2008)
An open economic system containing monopolies is investigated. A model of an economy with regular interests of consumers and taxation system is developed. The component of constant expenses in commodities production technologies is taken into account. The presence of consumption saturation of certain economy subjects is considered. An optimal solution of the equilibrium economy problem is presented on the basis of the mathematic model developed. A taxation strategy providing the optimal equilibrium state of economy is determined.